LACTIC ACID BACTERIES (LAB) OF YOGHURT ADDED WITH DAHLIA (Dahlia pinnata L) TUBER INULIN DECREASE - Dara, Widia; Alya Misdhal Rini; Intan Dwi Permata Sari (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Yogurt is a functional food product that contains probiotic bacteria. The functional value of yogurt can be enhanced by the addition of inulin from dahlia flower tubers, which has prebiotic content. Inulin is a water insoluble fiber. The purpose of this study was to analyze the organoleptic quality of yogurt added with dahlia flower tuber inulin and its physico-chemical properties. Experimental research type. There were three treatments in this study, namely the addition of dahlia flower inulin as much as 3, 5, and 7% and one control. Krusskall Wallis test was conducted to see the treatment differences in color, aroma, texture and taste of yoghurt. Objective observations included pH measurement, lactic acid content, LAB count and glucose test. Organoleptic test results showed that the most preferred yogurt in terms of color and texture was yogurt without the addition of inulin. The most preferred yogurt flavor and aroma was yogurt with 7% inulin added from dahlia flower tubers. The Krusskall Wallis test results showed no difference in all treatments on the color, aroma, texture, and taste of yogurt. There was no effect of adding inulin from dahlia flower tubers on organoleptic quality. Yoghurt added with 7% inulin at pH level, glucose test, lactic acid content, and lactic acid content increased. Total LAB decreased. Yogurt with 7% inulin added met SNI standards.